Representation of KRIS Policy in Indonesian Online Media Reporting: A Qualitative Content Analysis Study of 2025 Pre-Implementation - Rahayu, Eka Putri; Rahayu, Agustin Putri; Ariyanti, Rea (Panakeia Journal of Epidemiology, 2025)
The JKN standard inpatient class (KRIS) policy provides significant benefits for the Indonesian people, however, the implementation of KRIS in hospitals is a complex process and there are still many challenges that must be faced in the KRIS implementation plan. The determination of the KRIS policy based on Government Regulation Number 47 of 2021 concerning the Implementation of the Hospital Sector Article 84 letter b, will be implemented no later than January 1, 2023. However, the implementation of the BPJS Kesehatan KRIS has been postponed until January 1, 2025 so that hospitals can prepare the 12 standards that must be met when the KRIS service is officially opened in all hospitals in Indonesia. This research is expected explore on how is the pre-implementation policy of KRIS in Indonesia through Indonesian online news portals. This study used a qualitative analysis approach to online news portal content that aims to explain the KRIS policy in Indonesia. The sample of this study is national online media news about the KRIS policy published between January - May 2025. The researcher used the keyword "KRIS" and searched four (4) online news portals. MAXQDA software was also used as a data analysis tool in this study. The features used include Word Cloud and word frequency to understand the main concept. The results show that there are 7 dominant topics in the coverage of well-known online media in Indonesia related to the KRIS policy in Indonesia. The topic of KRIS policy challenges in Indonesia is the most dominant topic with 33 quotes (31%).